THE POWER OF LOVE AS A TRANSFORMATIVE FORCE: ALAIN BADIOU’S THEORY OF LOVE AND CIVIL RIGHTS MOVEMENT IN THE US - Syaebani, Muhammad Irfan; Yuwono, Untung; Ekosiwi, Embun Kenyowati (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
Love is never considered as a transformative force. Love is generally perceived merely as an affective-emotional thing and personal relationship. Love does not have any practical implication in transforming society. Through Alain Badiou’s theory of love, it can be demonstrated that love has the power to impact the world. According to Badiou, philosophy is a truth procedure that is always occurring in the arena. Politics, science, art, and love are the arenas in which philosophy operates. Thus, it is possible to talk about love philosophically. Philosophy aims to change the world since love is one of the arenas where philosophy operates. Based on the descriptive analysis method in interpreting Alain Badiou’s works; Being and Event and In Praise of Love, it implies that love can generate a transformative action. The case of miscegenation marriage between Mildred Jetter, an African-Indigenous American, and Richard Loving, a white male, during the civil rights movement in the US, can illustrate the role of love in transforming the world. Alain Badiou’s theory of love explains that love can transcend personal dimensions, and it is not purely a romantic feeling and personal relationship but also a transformative force. Thus, this study brings a new perspective on love theoretically and practically because love is not merely an emotion but also a force for change with social dimensions in practicality.